Comprehensive Physiology 2014
DOI: 10.1002/cphy.c130055
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Control of Gastrointestinal Motility and Secretion and Modulation of Gastrointestinal Functions

Abstract: Although the gastrointestinal (GI) tract possesses intrinsic neural plexuses that allow a significant degree of autonomy over GI functions, the central nervous system (CNS) provides extrinsic neural inputs that regulate, modulate, and control these functions. While the intestines are capable of functioning in the absence of extrinsic inputs, the stomach and esophagus are much more dependent upon extrinsic neural inputs, particularly from parasympathetic and sympathetic pathways. The sympathetic nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
388
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(418 citation statements)
references
References 557 publications
(704 reference statements)
4
388
0
5
Order By: Relevance
“…A previous study showed that preganglionic motor neurons provide vagal innervations to the gastrointestinal tract and stem from the dorsal motor nucleus of the vagus nerve within the brainstem. 12 Moreover, Lim et al reported that the colon transit time was delayed in patients with pontine lesions (a part of the brainstem). 58 Therefore, we suspected that the aberrations in the CR associated with the corticopontine tract may be linked with CNS dysregulation of colon transit time in constipated patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study showed that preganglionic motor neurons provide vagal innervations to the gastrointestinal tract and stem from the dorsal motor nucleus of the vagus nerve within the brainstem. 12 Moreover, Lim et al reported that the colon transit time was delayed in patients with pontine lesions (a part of the brainstem). 58 Therefore, we suspected that the aberrations in the CR associated with the corticopontine tract may be linked with CNS dysregulation of colon transit time in constipated patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data supporting different etiologies between FC and IBS-C are scant. A significant number of published studies have attributed the symptoms of functional gastrointestinal disorders (FGIDs) to dysregulation of the brain-gut axis (BGA) [10][11][12][13][14][15][16] that reflects a framework account for bidirectional interactions between the central nervous system (CNS), autonomic nervous system (ANS), and enteric nervous system (ENS). Within the framework, the CNS integrates communication within the BGA, thereby enabling the CNS to regulate the ENS via sympathetic and parasympathetic pathways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vagovagal reflexes are well described in gastrointestinal physiology (40). Vagal afferents activated by inflammation are believed to trigger a vagovagal reflex that elicits the CAP (41,42).…”
Section: Methodsmentioning
confidence: 99%